Hemodialysis Education Program Improves Compliance with Hemodialysis at Lavalette Hospital in Malang - Widyaningsih, Widyaningsih; Mawaddah, Nurul; Prastya, Anndy (Promotion and Prevention in Mental Health Journal, 2023)
Chronic renal failure is a condition of progressive decline in kidney function over months or years. The final stage of chronic renal failure is often referred to as End Stage Renal Disease (ESRD). If a patient has developed a severe stage of chronic renal failure, temporary therapy in the form of dialysis or hemodialysis is required to maintain their life. A major problem that contributes to hemodialysis failure is the problem of client compliance. This study aimed to determine the effect of Hemodialysis Program Education on Patient Compliance Undergoing Hemodialysis at Lavalette Hospital Malang. This study used a pre-experimental design method with the type of pre-test and post-test one-group design. With a total sample of 20 respondents. The results showed that most of the respondents in the Hemodialysis Room of Lavalette Hospital Malang City had moderate compliance before being given education, as many as 16 respondents (80%). Most of the respondents in the Hemodialysis Room of Lavalette Hospital Malang City had moderate compliance after being given education, as many as 13 respondents (65%). The Wilcoxon test results obtained a p <0.05, namely p = 0.002, which means that there is an Effect of Hemodialysis Program Education on Compliance Following the Hemodialysis Program at Lavalette Hospital Malang. It is recommended that HD nurses create a WhatsApp group as a medium for delivering information and can help remind patients to carry out the hemodialysis program when not at the dialysis center (at home) to increase compliance and improve the quality of life of patients undergoing HD.